The Latest Discoveries of the Parker Solar Probe Confirm the Predictions of My Model of Solar Activity and My Concept of the Universe Creation (Global Journal of Science Frontier Research, 2023)
Abstract not found
Keywords: parker solar probe (PSP); PSP confirmed my predictions